Pengaruh Kualitas Layanan Mobile Banking BNI terhadap Kepuasan Nasabah PT. Bank Negara Indonesia (Persero) Tbk. Kantor Kas Boulevard Makassar - Halida Sasmita; Nurfadilah Nurfadilah; Karta Negara Salam; Dhita Pratiwi AR; Kevin William Marcello (LP2M IBK Nitro, 2023)
The purpose of this study was to determine the effect of BNI mobile banking service quality on customer satisfaction at PT Bank Negara Indonesia (Persero) Tbk. KK Boulevard Branch Office Makassar. The type of research used in this research is qualitative. With a sample of 100 respondents using convenience sampling technique and the analysis method used is simple linear regression analysis. The results showed that: the quality of BNI mobile banking services (X1) has a positive and significant effect on customer satisfaction at PT Bank Negara Indonesia (Persero), Tbk. KK Bouluvard Branch Office Makassar.